The IMPACT OF ENVIRONMENTAL AND FINANCIAL PERFORMANCE ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Rania Kharissa Lutfia, Nyimas; Friyani, Rita; Dian Maisyarah, Nyimas (Journal of Business Studies and Management Review, 2026)
This study examines the effect of environmental performance and financial performance on Corporate Social Responsibility (CSR) disclosure among consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. Environmental performance was measured using the PROPER (Program Penilaian Peringkat Kinerja Perusahaan dalam Pengelolaan Lingkungan Hidup) rating system, while financial performance was proxied by Return on Assets (ROA). CSR disclosure was measured using the GRI 4 framework. Using a purposive sampling technique, 24 companies were selected, yielding 72 observations. After outlier removal and data transformation, 57 valid observations were analysed using multiple linear regression with SPSS 27. Results showed that environmental performance and financial performance did not simultaneously exert a significant effect on CSR disclosure. The model explained only 7.7% of CSR disclosure variation (R² = 0.077), suggesting that institutional pressure, regulatory compliance, and stakeholder legitimacy are more decisive drivers of CSR disclosure than environmental or financial performance alone.